Polyhouse Agricultural Marketing System Using Big Data Hadoop - Ayesha Bhandralia; Resham Arya; S. N. Panda; Sachin Ahuja (International Journal of Advances in Applied Sciences, 2016)
Agriculture is to cultivate and produce crops and livestock products. Agriculture in its associated sectors is unquestionably the largest livelihood provider, in the broad areas of rural India. With the emergence of high tech agriculture farming known as Polyhouse farming came into existence. Polyhouse farming is an alternative new technique which reduces clinging on to natural procedures that are very basic needs of agriculture i.e. rainfall, temperature, humidity and geographical conditions and this result in the most advantageous use of water and land resources. Polyhouse advances to create suitable microclimates, which favour the crop production by simulation of artificial environment using latest computer assisted technology. Yet polyhouse product marketing is an uncovered area which is still neglected and there is a strong need to for an effective marketing intervention or channelization. The liberalized trade environment in general has added another dimension to the poverty of farmers and uncertainty about the future. The paper describes the long established approach of marketing concept of polyhouse agriculture. The relationship between development, marketing and accessibility in polyhouse agriculture is reviewed. We have detected various inadequate parameters, and recognized the need of an effective polyhouse marketing system which may have beneficial impact on farmers.